Implementing Metacognitive based Guided Inquiry on Chemistry to Increase Student’s Critical Thinking Skills - Winarti, Atiek; Hasna , Baiti; Suharto, Bambang (International Journal of Psychosocial Rehabilitation, 2020)
Critical thinking skills (CTS) are indispensable skills for dealing with the Industrial Revolution 4.0 era. Unfortunately, learning methods implemented by teachers in schools have not specifically focused on the development of these skills. This study aims to determine the effect of metacognitive-based Guided Inquiry (GI) learning on students’ CTS and achievement in chemistry. The study applied the pre-test post-test control group design method. The sample consists of 66 11th grade students of Madrasah Aliyah Negeri 1 (MAN 1) Banjarmasin, Indonesia. The data were collected using achievement tests, critical thinking tests, and attitude observation sheets. Then, the data was analyzed by using percentage and t-test. The results showed that (1) through metacognitive-based GI learning, students’ CTS in the experimental class developed better than in the control class. The percentage of students who have the highest level of critical thinking in the experimental class is greater than those in the control class. (2) In the experimental class, all affective indicators measured, namely curiosity, cooperation, and responsibility, achieved a very good category. Meanwhile, in the control class, the cooperation indicator is the only indicator that is in the good category. (3) The level of students’ learning success in cognitive, affective, and psychomotor in the experimental class is higher than in the control class. It implies that integrating metacognition into the stages of learning activities should be the solution to CTS development.